2012
DOI: 10.1136/annrheumdis-2011-200574
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic association of theVTCN1region with rheumatoid arthritis

Abstract: These results indicate a novel genetic association with the VTCN1 region in RA susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…VTCN1 rs10923223 polymorphism has also been associated with disease course in JIA [53]. In support of a critical role for this gene in inflammatory arthritis, variants in VTCN1 were found to be associated with RA in a Dutch cohort [55]. …”
Section: Genetics Of Oligoarticular Jia/polyarticular Rf-negative Jiamentioning
confidence: 99%
“…VTCN1 rs10923223 polymorphism has also been associated with disease course in JIA [53]. In support of a critical role for this gene in inflammatory arthritis, variants in VTCN1 were found to be associated with RA in a Dutch cohort [55]. …”
Section: Genetics Of Oligoarticular Jia/polyarticular Rf-negative Jiamentioning
confidence: 99%
“…Outside the MHC, several suggestive associations in ACPAÀ disease have been reported [26][27][28], and a genome-wide significant association has been found at the locus including ANKRD55 GWAS results have highlighted regulatory T cells and CD4 þ memory T cells as critical cell types in RA.…”
Section: Rheumatoid Arthritis Risk Loci Outside the Mhcmentioning
confidence: 99%
“…The GWAS failed to identify specific susceptibility loci to ACPA-negative RA beyond the GWAS significance level. Several studies from mainly European countries using candidate gene approach have reported susceptibility markers to ACPA-negative RA [ 26 - 30 ], but none of them were specific to ACPA-negative RA with strong P -values, due to their limited numbers of subjects.…”
Section: Introductionmentioning
confidence: 99%